2010
DOI: 10.1007/s00418-010-0706-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunoelectron microscopic and computer-assisted image analyses to detect advanced glycation end-products in human myocardium

Abstract: Advanced glycation end-products (AGEs) result from oxidation-reduction reactions that ensue when a sugar becomes adducted to a protein. AGEs cause various complications of diabetes mellitus (DM). Experimental and clinical evidence suggest that AGEs also contribute to the complications of hypertension (HTN). Little is known about the abundance and localization of AGEs in human myocardium. In a few light microscopic studies, the AGE carboxymethyl lysine (CML) has been immunolabeled and localized virtually exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
0
21
1
Order By: Relevance
“…36 When light microscopic visualization of CML was implemented with electron microscopy, vascular deposition of CML was recently shown to be accompanied by interstitial accumulation of CML, which can directly reduce myocardial diastolic distensibility because of collagen crosslinking. 37 The findings of the present study differ from a previous study in HFREF and HFNEF patients free of coronary artery disease. 3 In the present study, DM worsened diastolic LV dysfunction in AS through fibrosis, AGE deposition, and raised cardiomyocyte F passive .…”
Section: Mechanisms Of Diastolic Left Ventricular Dysfunction In Aortcontrasting
confidence: 99%
“…36 When light microscopic visualization of CML was implemented with electron microscopy, vascular deposition of CML was recently shown to be accompanied by interstitial accumulation of CML, which can directly reduce myocardial diastolic distensibility because of collagen crosslinking. 37 The findings of the present study differ from a previous study in HFREF and HFNEF patients free of coronary artery disease. 3 In the present study, DM worsened diastolic LV dysfunction in AS through fibrosis, AGE deposition, and raised cardiomyocyte F passive .…”
Section: Mechanisms Of Diastolic Left Ventricular Dysfunction In Aortcontrasting
confidence: 99%
“…Intra-operative LV anterior wall epicardial biopsies were obtained as previously described (39, 40). Patients recruited to this protocol were part of an NIH grant (RO1HL089944) with multiple specific aims; therefore, biopsy samples were allocated to several protocols, data from some of which have been published 39, 40 . Given the size of each biopsy, all protocols could not be performed on each biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…Anterior LV free wall epicardial biopsies weighing ∼25-50 mg were obtained during CABG soon after the patient was placed on cardiopulmonary bypass, as previously described 39,40 . The biopsy was placed in oxygenated HEPES-based Krebs buffer containing 30 mmol/L 2,3-butanedione monoximine (BDM) at room temperature 39, 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Applying immunoelectron microscopy using an anti-carboxymethyl lysine (CML) antibody (CML is a major antigenic AGE structure) to localize and quantify CML in myocardial tissue obtained by epicardial biopsy during coronary bypass grafting (CBG), CML was found to be scattered throughout cardiomyocytes in all patients (independent of HTN or DM) and in endothelial cells. With CML being very prevalent in CBG patients, Donaldson et al (2010) concluded that AGEs could play a role in abnormal cardiomyocyte function. Franz et al (2010b) looked at chronic cardiac allograft rejection (CCAR), which is represented by cardiac allograft vasculopathy (CAV) and Wbrosis and zoomed into associated problems, i.e.…”
Section: Heart and Blood Vesselsmentioning
confidence: 98%
“…Abundance and distribution of advanced glycation endproducts (AGEs) were analysed by Donaldson et al (2010) in the human myocardium. AGE formation and accumulation are most accelerated under diabetes mellitus (DM), thus contributing to various complications (van Heerebeek et al 2008).…”
Section: Heart and Blood Vesselsmentioning
confidence: 99%